A “Wear and Tear” Hypothesis to Explain Sudden Infant Death Syndrome - Elhaik, Eran (Frontiers in Neurology, 2016)
Sudden Infant Death Syndrome (SIDS) is the leading cause of death in USA infants under one year of age accounting for approximately 2,700 deaths per year. Although formally SIDS dates back at least 2,000 years and was even mentioned in the Hebrew Bible (Kings 3:19) its etiology remains unexplained prompting the CDC to initiate a sudden unexpected infant death case registry in 2010. Due to their total dependence, the ability of the infant to allostatically regulate stressors and stress responses shaped by genetic and environmental factors is severely constrained. We propose that SIDS is the result of cumulative painful, stressful, or traumatic exposures that begin in utero and tax neonatal regulatory systems incompatible with allostasis. We also identify several putative biochemical mechanisms involved in SIDS. We argue that the important characteristics of SIDS, namely male predominance (60:40), the significantly different SIDS rate in USA Hispanics (80% lower) compared to whites, 50% of cases occurring between 7.6 and 17.6 weeks after birth with only 10% after 24.7 weeks, and seasonal variation with most cases occurring during winter, are all associated with common environmental stressors, such as neonatal circumcision and seasonal illnesses. We predict that neonatal circumcision is associated with hypersensitive to pain and decreased heart rate variability which increase the risk for SIDS. We also predict that neonatal male circumcision will account for the SIDS gender bias and that cultures that practice high male circumcision rates, like USA whites, will have higher SIDS rates compared to cultures with lower circumcision rates. SIDS rates will also be higher in USA states where Medicaid covers circumcision and lower among cultures that do not practice neonatal circumcision and/or cannot afford to pay for circumcision. We last predict that winter-born premature infants who are circumcised will be at higher risk of SIDS compared to infants who experience fewer nociceptive exposures. All these predictions are testable experimentally using animal models or cohort studies in humans. Our hypothesis provides new insights into novel risk factors for SIDS that can reduce its risk by modifying current infant care practices to reduce nociceptive exposures.